Implementation and impact of NHS-funded tobacco dependence services in England: a mixed-method evaluation protocol - Kate Jolly; Tomos Robinson; Sheena E Ramsay; Sarah Damery; Eileen F S Kaner; Sarah Flanagan; Chris Armitage; Jane West; Ailsa Rutter; Mackenzie Fong; Angela S Attwood; Sally Bridges; et al. (BMJ Open)
Introduction Tobacco smoking remains a leading cause of ill-health, premature mortality and a driver of health inequalities. To support smokers in England, a comprehensive approach to treating tobacco dependence is being implemented. This includes offering support to all people admitted to hospitals, as well as women and pregnant people within NHS settings. We aim to describe the protocol for an evaluation of this tobacco-dependence service.Methods and analysis This is a national evaluation across five regions in England (i.e., South West, West Midlands, Greater Manchester, North East and North Cumbria, Yorkshire and Humber) including 11 NHS Foundation Trusts. It is funded from September 2021 to September 2025. Evaluation settings are acute hospital, maternity and inpatient mental health.Work package (WP) 1 involves qualitative key informant interviews to characterise the policy implementation context. WP 2 involves an online survey to assess the routinisation of the service in practice and staff attitudes regarding tobacco dependence, plus in-depth interviews with relevant practitioners to explore survey findings and interviews with smokers to investigate its usefulness and impact. WP 3 involves descriptive statistical analysis of routinely collected data to assess service uptake and impact on health and care outcomes (e.g., smoking status). WP 4 involves an economic analysis of routinely collected data to determine the financial impact of the service. Qualitative data (WP 1, WP 2) will be analysed using Thematic Analysis and Framework Analysis, respectively. WP 2 survey data will be analysed using descriptive statistics.Ethics and dissemination This evaluation received favourable ethical opinion from Newcastle University (17756/2021) and NHS Wales Research Ethics Committee (22/WA/0203). It has also received Confidentiality Advisory Group support (22CAG0103).